Beyond Islamic Finance: Developing Disruptive and Collaborative Business Models in Modern Islamic Economic Thought - The Case of Konya Seker - İsa Yılmaz (Türkiye İslam İktisadı Dergisi)
The idea of modern Islamic economics institutionalized through the expansion of banking sector in the post-war period. While this provides some advantages in terms of catching up the global financial development, it also poses a serious threat since bank-based development leaves institutional development in other sectors of real economy rudimentary. Recalling its initial promises to generate socioeconomic justice, Islamic economics aims to strengthen a collaborative economy understanding, which emphasizes authentic business initiatives that are disruptive in terms of thinking beyond the neoclassical market logic. This paper, accordingly, suggests the case of Konya Seker, a joint-stock company operating under Anadolu Birlik Holding, as a disruptive and collaborative business model that symbolizes a success story in Turkish business sector as to how a mediocre subsidiary of some beet growers’ cooperatives has eventually turned into an agricultural industry giant by pushing the limits of domestic economy and hence making inroads innternational business environment. Konya Seker’s model implies that a partnership-based collaborative business understanding disrupts the capitalist market structure through holding an equity-efficiency equilibrium, and hence offers fair distribution of profits amongst its stakeholders. In a wider sense, this model helps realize the old developmentalist promises of Islamic economics and suggests an alternative to the bank-based solutions to the socioeconomic problems of Muslim societies.